2021
DOI: 10.1183/16000617.0023-2021
|View full text |Cite
|
Sign up to set email alerts
|

Future concepts in bronchodilation for COPD: dual-versusmonotherapy

Abstract: Most patients with COPD are recommended to initiate maintenance therapy with a single long-acting bronchodilator, such as a long-acting muscarinic antagonist or long-acting β2-agonist. However, many patients receiving mono-bronchodilation continue to experience high symptom burden, suggesting that patients are frequently not receiving optimal treatment. Treatment goals for COPD are often broad and not individually tailored, making initial treatment response assessments difficult. A personalised approach to ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 99 publications
0
2
0
2
Order By: Relevance
“…17,18 Studying a set of different effects simultaneously in the pharmacological management of COPD has also been encouraged in several reviews and statements since the relationship between spirometry and symptoms appears to be modest. [19][20][21] Moreover, recently, a multicomponent measure for assessing disease worsening in COPD has been studied in the IMPACT trial. 22 Han et al demonstrated that prevention of clinically important deterioration (defined as any of the following on-treatment events: moderate/severe exacerbation, deterioration in lung function or deterioration in health status) is likely to reduce future risks of exacerbations requiring hospitalization and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Studying a set of different effects simultaneously in the pharmacological management of COPD has also been encouraged in several reviews and statements since the relationship between spirometry and symptoms appears to be modest. [19][20][21] Moreover, recently, a multicomponent measure for assessing disease worsening in COPD has been studied in the IMPACT trial. 22 Han et al demonstrated that prevention of clinically important deterioration (defined as any of the following on-treatment events: moderate/severe exacerbation, deterioration in lung function or deterioration in health status) is likely to reduce future risks of exacerbations requiring hospitalization and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A dupla broncodilatação LAMA/LABA, em comparação com a monoterapia com LAMA ou LABA, e para um perfil de segurança similar, demonstra maior eficácia com superior melhoria da função pulmonar, redução dos sintomas, do número de agudizações, de hospitalizações e da deterioração clínica. 1,6,[8][9][10] A dupla broncodilatação é a terapêutica de primeira linha em doentes sintomáticos ou com intolerância ao exercício e nos doentes com classificação GOLD B e E. As opções de terapêutica combinada em associação fixa atualmente disponíveis são: o aclidínio/formoterol (ge-nuair®), o glicopirrónio/indacaterol (breezhaler®), o tiotrópio/olodaterol (respimat®), o umeclidínio/vilanterol (ellipta®) e o glicopirrónio/formoterol (aeros-phere®).…”
Section: Terapêutica Farmacológica Inalada Em Portugalunclassified
“…Таким образом, сегодня мы располагаем многочисленными свидетельствами того, что фиксированные комбинации ДДБА/ДДХБ обеспечивают оптимальную бронходилатацию и играют первостепенную роль в предотвращении обострений ХОБЛ. Превосходя плацебо и активный контроль (ДДБА, ДДХБ, ИГКС/ДДБА), комбинированные бронходилататоры могут отличаться по своему терапевтическому потенциалу, хотя имеющаяся доказательная база (неравнозначная по числу, масштабу и дизайну исследований), в т. ч. и единичные прямые сравнительные исследования, не позволяет сделать в каждом конкретном случае однозначный выбор в пользу той или иной фиксированной комбинации ДДБА/ДДХБ [24][25][26][27].…”
Section: ддба/ддхб: выбор лучшего из возможногоunclassified